Chronic HCV Infection: Clinical Advances and Eradication Perspectives - Liberto, Maria Carla; Marascio, Nadia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Hepatitis C virus (HCV) chronic infection can determine liver fibrosis, cirrhosis and hepatocellular carcinoma, as well as several extra-hepatic manifestations (i.e., mixed cryoglobulinemia, metabolic syndrome, kidney disease, etc.). HCV infection is asymptomatic until severe stages of disease, thus screening policy in the general population and in specific risk categories is necessary to allow for timely intervention. Despite a high sustained virological response by direct-acting antiviral drugs, a limited percentage of treated subject failed therapy according to resistance associated substitution carried on viral isolates and comorbidities in infected patients. Therefore, tailored therapy is required to cure HCV infection. Failure to comply with these conditions may impair success of HCV eradication expected by 2030. This Special Issue aims to discuss eradication perspectives related to therapy efficacy in patients with chronic diseases, developments in diagnostic procedures and improvements in screening policy.